“At least we have something to discuss over lunch…” The implications for knowledge management when implementing a new library system. A Norwegian experience. - Johannessen, Hilde Terese Drivenes (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This article investigates how staff and management in Norwegian academic libraries have experienced the implementation of the new library management system Alma. As a new library management system is introduced, the need for learning on demand emerges. An anonymous survey was sent to all academic libraries in Norway, resulting in a total of 626 responses. This article presents the findings from this survey and provides some reflections on how a firm grip on knowledge management could have helped make such a transition easier.